Factors related to behavior Disposal of Garbage in health staff based on health belief model - Arezoo Nejaei; samad Babaiy2; moradali zareipour (Mashhad University of Medical Sciences, 2018)
Introduction: One of the most important factors in maintenance and promotion of public health is sanitary disposal of waste. At present, the use of educational models to determine the causes of non-acceptance of health-related behaviors is growing. This study aims to evaluate the factors associated with behavior of garbage disposal based on health belief model in Urmia city health center staff. Materials and Method: This descriptive-analytic study was took place on 300 employees in 2016 in Urmia city health center. Samples were collected using simple random sampling method. Also, data gathering was done in accordance with a questionnaire containing demographic questions and the health belief model structures. the validity and reliability of the used questionnaire was confirmed by the researchers. Statistical data analysis was performed using software spss-16 through chi-square tests and logistic regression analysis.   Results: According to the obtained results there was a significant relation among dependent variable (sanitary garbage disposal) and surveyed independent variables including gender, marital status, employment category, socioeconomic status (P